Artemannuols A–C, novel sesquiterpenoid–flavonol hybrids with antihepatoma activity from Artemisia annua - He, Xiao-Feng; Wang, Meng-Fei; Li, Tian-Ze; Ma, Yun-Bao; Chen, Ji-Jun (Organic & biomolecular chemistry, 2023)
Artemisia annua , also known as “Qinghao” in Chinese, is a famous traditional Chinese medicine and has been used for the treatment of malaria and various tumors. In this study, three novel sesquiterpenoid–flavonol hybrids, artemannuols A–C (1–3), were isolated and elucidated by extensive spectral data and ECD calculations. Structurally, artemannuols A–C (1–3) are the first examples of sesquiterpenoid–flavonol hybrids fused by an ether bond, among which artemannuols A and B (1 and 2) are composed of bisabolane-type sesquiterpenoid and flavonol moieties, and artemannuol C (3) is composed of humulane-type sesquiterpenoid and flavonol moieties. The antihepatoma assay suggested that compounds 1–3 showed inhibitory effects against HepG2, Huh7, and SK-Hep-1 cell lines with IC 50 values in the range of 32.7 to 70.4 μM.